Prevalence of rheumatic heart disease in North‐Central Nigeria: a school‐based cross‐sectional pilot study. Issue 11 (9th September 2020) - Nkereuwem, Esin; Ige, Olukemi O.; Yilgwan, Christopher; Jobe, Modou; Erhart, Annette; Bode‐Thomas, Fidelia
Abstract: Objectives: To present epidemiological data on rheumatic heart disease (RHD), the most common acquired heart disease in children and young adults in low‐ and middle‐income countries, for North‐Central Nigeria. Methods: In this pilot study, we conducted clinical and echocardiography screening on a cross section of randomly selected secondary schoolchildren in Jos, North‐Central Nigeria, from March to September 2016. For outcome classification into borderline or definite RHD, we performed a confirmatory echocardiography using the World Heart Federation criteria for those suspected to have RHD from the screening. Results: A total of 417 secondary schoolchildren were screened, of whom 247 (59.2%) were female. The median age was 14 years (IQR: 13–15). Clinical screening detected 8/417 children, whereas screening echocardiography detected 42/417 suspected cases of RHD. Definitive echocardiography confirmed 9/417 with RHD corresponding to a prevalence of 21.6 per 1000 (95% CI, 6.7–36.5). All but one of the confirmed RHD cases (8/9) were borderline RHD corresponding to a prevalence of 19.2 per 1000 (95% CI, 8.3–37.5) for borderline RHD and 2.4 per 1000 (95% CI, 0.1–13.3) for definite RHD. RHD was more common in boys and cardiac auscultation missed over 50% of the cases. Conclusions: This study showed a high prevalence of RHD among secondary schoolchildren in North‐Central Nigeria with a vast predominance of asymptomatic borderline lesions. Larger school‐based echocardiography screening using portable or handheld echocardiography aimed at early detection of subclinical RHD should be adopted. Abstract : Objectifs: Présenter des données épidémiologiques sur la cardiopathie rhumatismale (CR), la maladie cardiaque acquise la plus courante chez les enfants et les jeunes adultes dans les pays à revenus faibles et intermédiaires, pour le centre‐nord du Nigéria. Méthodes: Dans cette étude pilote, nous avons effectué un dépistage clinique et échocardiographique sur un échantillon transversal d'élèves du secondaire sélectionnés aléatoirement à Jos, dans le centre‐nord du Nigéria, de mars à septembre 2016. Pour la classification des résultats en CR limite ou définitive, nous avons effectué une échocardiographie de confirmation en utilisant les critères de la Fédération Mondiale du Cœur pour les personnes suspectées d'avoir une CR lors du dépistage. Résultats: Au total, 417 élèves du secondaire ont été dépistés, dont 247 (59, 2%) étaient des filles. L'âge médian était de 14 ans (IQR: 13‐15). Un dépistage clinique a détecté 8/417 enfants, tandis qu'un dépistage par échocardiographie a détecté 42/417 cas suspects de CR. L'échocardiographie a confirmé une CR définitive chez 9/417, correspondant à une prévalence de 21, 6 pour 1000 (IC95%: 6, 7 à 36, 5). Tous les cas confirmés de CR sauf un (8/9) étaient limites, correspondant à une prévalence de 19, 2 pour 1000 (IC95%: 8, 3 à 37, 5) pour une CR limite et 2, 4 pour 1000 (IC95%: 0, 1 à 13, 3) pour une CR définitive. La CR était plus fréquente chez les garçons et l'auscultation cardiaque a manqué plus de 50% des cas. Conclusions: Cette étude a montré une prévalence élevée de CR parmi les enfants du secondaire dans le centre‐nord du Nigeria avec une forte prédominance de lésions asymptomatiques limites. Un dépistage échocardiographique à plus grande échelle en milieu scolaire utilisant une échocardiographie portable ou manuelle visant à la détection précoce de la CR subclinique devrait être adopté.